Licorice Micro Site Production in Afghanistan - Zahirian, Gul Ahmad (Journal of Natural Sciences – Kabul University, 2025)
Licorice is an important medicinal plant. Its native habitat is found in dry, scrubby areas. In Afghanistan, licorice grows only in the wild. Licorice is consumed worldwide, with the main importers located in Western markets. The source of licorice powder is extracted from the root and used in sweets, baked goods, ice cream, soft drinks, and more. Afghanistan is an important exporter of licorice roots, with Pakistan and India being the primary regional markets for Afghan licorice and other wild plants. Afghanistan mainly exports roots at a low price, while other countries focus on less processing of the roots and extracts, leading to higher pricing.